Berpengaruhkah Pajak Daerah, Retribusi Daerah Dan Hasil Pengelolaan Kekayaan Daerah Yang Dipisahkan Terhadap Pendapatan Asli Daerah? - Riszky Agustin Rizalni; Elva Dona (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this study was to examine the effect of local taxes, local levies and the results of the management of separated regional assets on local revenue in the district / city of West Sumatra in 2019-2021. The object of this research is the district / city government of West Sumatra. The data used is secondary data taken from the realization report of local government revenue at the West Sumatra Central Statistics Agency (BPS). The type of data used is panel data. The population and sample amounted to 19 districts / cities of West Sumatra using total sampling technique. The results showed that local taxes had a significant effect while local levies, the results of the management of separated regional assets had no significant effect on local revenue and together had a positive and significant effect on local revenue in the district / city of West Sumatra.